(untitled) (Research, Society and Development, 2019)
The purpose of this research is to find out the effect of learning model and task assessment regarding achievement of science by controlling student prior knowledge.This research is experimental which have factorial design 2 x 2. Samples for this research are students who had contracted basic concepts of science. The sample taken by Simple Random Sampling. Afterward, the results showed that: (1) science learning outcomes of student which have been taught using Jigsaw cooperative models are higher than those taught using STAD cooperative model by controlling student prior knowledge, (2) science learning outcomes of students who are assessed using structured assessment are higher than those assessed using portfolio asssessment by controlling student prior knowledge, (3) there is an interaction effect between learning model and the task assessment on achievement of students in learning science by controlling student prior knowledge, (4) science achievement of students who have been taught using Jigsaw model are higher compared to those taught using STAD models for the group of students with assess using structured assessment by controlling student prior knowledge, (5) science achievement of students who have been assessed using structured assessment are lower compared to those who assessed using portfolio assessment for the group of students with taught using STAD model by controlling student prior knowledge. Thus, the linier effect of prior knowledge on student learning outcomes of science does not have significant difference between four groups of students formed by learning model and intelligence..